Risk Factors for Surgical Site Infection in Abdominal Surgery : A Systematic Review - Fauzi Alhuda; Afina Kamilia; Vivi Yovita (The International Journal of Medical Science and Health Research, 2026)
Introduction: Surgical site infection (SSI) remains the most common postoperative complication in abdominal surgery, associated with increased morbidity, mortality, and healthcare costs. Identifying modifiable and non-modifiable risk factors is essential for targeted prevention. Methods: This systematic review synthesized data from 80 studies including RCT, etc across colorectal, gastric, cesarean, bariatric, hysterectomy, ventral hernia, appendectomy, and emergency laparotomy populations. Outcome measures were odds ratios (OR), relative risks (RR), and 95% confidence intervals (CI) for SSI. Results: Patient-related significant positive risk factors included obesity (BMI>30 kg/m², RR=1.60, 95%CI:1.47-1.74) (1), diabetes mellitus (RR=1.65, 95%CI:1.24-2.20) (1), hypoalbuminemia (OR=3.05,95%CI:2.08-4.49) (2), and ASA score ≥3 (RR=1.34,95%CI:1.19-1.51) (1). Perioperative factors with largest effect sizes included operative duration ≥3 hours (OR=8.33,95%CI:3.81-18.20) (2), blood transfusion (RR=2.03,95%CI:1.34-3.06) (1), open versus laparoscopic approach (RR=1.81,95%CI:1.57-2.10) (1), emergency versus elective surgery (RR=1.36,95%CI:1.19-1.55) (1), stoma formation (RR=1.89,95%CI:1.28-2.78) (1), and contaminated/dirty wound class (OR=4.5,95%CI:1.8-11.5) (4). Protective interventions included oral+IV antibiotics (RR=0.47,95%CI:0.40-0.56) (6), wound edge protectors in contaminated cases (RR=0.44,95%CI:0.28-0.67) (15), glove/instrument change before closure (aRR=0.87,95%CI:0.79-0.95,p=0.0032) (70), and triclosan-coated sutures (OR=0.84,95%CI:0.75-0.93) (50). High FiO₂ showed benefit only when mean BMI<30 and diabetic prevalence<20% (19). Discussion: Operative duration is the single most potent risk factor, possibly aggregating multiple mechanisms. Obesity-diabetes interactions attenuate supplemental oxygen benefits. Bundle RCTs paradoxically showed harm or no benefit, contrasting with observational data. Conclusion: SSI risk in abdominal surgery is driven by obesity, diabetes, prolonged operation, open approach, emergency status, and contamination. Prevention should prioritize antibiotic optimization, minimally invasive techniques, and contamination-reducing intraoperative maneuvers.